Pelaksanaan Pendidikan dan Pelatihan Terhadap Kinerja Guru Madrasah di Kota Gorontalo - Mujizatullah, Mujizatullah; Mustolehudin, Mustolehudin (Badan Litbang dan Diklat Kementerian Agama RI, 2019)
AbstractThis study aimed to find out the influence level of subject teachers’ training and education for the improvement of madrasah teacher’s performance in Gorontalo. This study used a survey and quantitative research method. The result of this research showed that training and education implementation had influenced the madrasa teacher’s performance in Gorontalo. There was an increase in madrasa teacher's four competencies after they joined the training, which are pedagogical competence, personality competence, professional competence, and social competence. Respondents said that the trainers (widyaiswara) could explain the material substance well (score 4.4). The trainers have much understood and competent in the training aims and procedures. So, the academic qualification of the trainers is appropriating with their primary tasks by involving qualified and professional instructors. Nevertheless, some trainers were not mastering in presenting training material. Furthermore, the training materials are considering inadequate for the training participants. AbstrakPenelitian ini bertujuan untuk mengetahui tingkat pengaruh pendidikan dan pelatihan mata pelajaran terhadap peningkatan kinerja guru madrasah di Kota Gorontalo. Metode yang digunakan dalam penelitian ini adalah survei dan metode kuantitatif. Hasil penelitian menunjukkan bahwa pelaksanaan pendidikan dan pelatihan terhadap guru madrasah di Kota Gorontalo, memiliki pengaruh terhadap kinerja guru. Pengaruh tersebut adalah guru memiliki peningkatan dalam kompetensi pedagogik, kompetensi kepribadian, kompetensi profesional, dan kompetensi sosial setelah mengikuti kediklatan. Responden menjelaskan bahwa widyaiswara mampu menyampaikan materi dengan baik dengan skor 4,4. Widyaiswara cukup memahami dan menguasai tujuan dan prosedur penyelenggaraan diklat sehingga kualifikasi akademik widyaiswara sesuai dengan tugas pokoknya dengan melibatkan instruktur yang kompeten dan profesional. Namun demikian, masih terdapat beberapa Widyaiswara dalam pelaksanaan diklat dianggap masih kurang memadai dalam membawakan materi. Selain itu, ketersediaan bahan ajar bagi peserta diklat dianggap masih kurang memadai.